Gestión estratégica de microempresas del sector agroindustrial en Tabasco, México - Suárez Reyes, Susana (2021)
Agroindustrial microenterprises are one of the key sectors in the country’s economy, generating jobs and contributing to regional and national development, however, the limitations and short lifespan these companies have is worrying. The study presents an analysis of the strategic management of 194 microenterprises in the agro-industrial sector of Villaher-mosa, Tabasco. The results show that these companies have deficiencies at two stages of this process, the formulation and implementation of strategies, as managers do not plan their activities or set their short, medium and long goals. The lack of an organizational philosophy is detected, which can affect the optimal functioning of the organization.